Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian Pengguna Marketplace Shopee - Fajri, Hillan Muhammad; Suherman, Jajang (Jurnal Dimamu, 2025)
Shopee is a marketplace that is often visited throughout 2023 among other marketplaces, even though Shopee is the most visited marketplace, there are still many complaints experienced by consumers regarding product purchases at Shopee, inconsistent product quality problems and prices that are not in accordance with product quality. This study aims to determine the influence of price and product quality on simultaneous or partial purchase decisions on the Shopee application. The method used in this study is quantitative with the type of primary data and uses data collection techniques in the form of observation, interviews and questionnaires. Meanwhile, the sampling technique is non-probability sampling. The object of the research was the people in Solokanjeruk Village who were active in online shopping on the Shopee marketplace which amounted to 9,622 people with a sample of 100 people. The results of the research of Shopee users in Solokanjeruk Village show that there is a significant influence between the price on the purchase decision of 54.4% for the R2 test and the results of the t-test where the value of t is calculated > t tabel (10.811 > 1.984) meaning that Ha1 is accepted, there is a significant influence between product quality on the purchase decision of 49.9% for the R2 test with the results of the t-test where the t-value is > ttabel (9.889 > 1.984) means that Ha2 is accepted,  and simultaneously there was a significant influence between price and product quality on purchase decisions of 61.9% for the R2 test with the results of the F test where the F value was calculated > F tabel (78.913 > 2.36).